Innovation of Islamic Religious Education Learning Through the Quantum Teaching Method at UPT SDN 18 Kalosi - Asran Asran; Andi Abd. Muis; Sumadin Sumadin; Amaluddin Amaluddin; Raya Mangsi (CV. Gerasi Insan Nusantara, 2026)
This study aims to analyze the implementation of the Quantum Teaching method in Islamic Religious Education (IRE) learning, explore teachers’ and students’ experiences and perceptions toward its application, and identify learning innovations developed through the integration of the method at UPT SDN 18 Kalosi, Enrekang Regency. This study employed a qualitative descriptive approach within a constructivist paradigm. Data were collected through classroom observations, semi-structured interviews, documentation, and field notes involving the principal, Islamic Religious Education teacher, classroom teachers, and students. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the Quantum Teaching method significantly enhanced students’ engagement, motivation, and understanding of Islamic Religious Education. Learning became more interactive and student-centered through storytelling, group discussions, role-playing, project-based learning, and the integration of digital media. Students demonstrated stronger critical thinking, communication skills, and the ability to apply Islamic values in daily life. Teachers and students expressed positive perceptions of the method, although challenges related to limited instructional time, technological facilities, and differences in student abilities were identified. The study suggests that Quantum Teaching can serve as an effective instructional strategy for improving the quality of Islamic Religious Education, particularly in elementary schools. The findings encourage schools to strengthen teacher professional development and provide adequate technological support to facilitate innovative and meaningful learning experiences. This study contributes to the literature by demonstrating how Quantum Teaching can be adapted within Islamic Religious Education to foster active participation, contextual understanding, and the internalization of religious values. The study provides an innovative pedagogical model that integrates student-centered learning, educational technology, and character development in elementary Islamic education.